The Impact of Financial Technology Development on Micro, Small, and Medium Enterprises in Ternate City - Agatha Christy Situru; Zandy Zain; Hijrasil; Muhammad Alwi Hapri; Abi Suar (Universitas Sulawesi Barat, 2026)
This study focuses on the impact of Financial Technology (fintech) developments on the performance and growth of Micro, Small, and Medium Enterprises (MSMEs) in Ternate City. The rapid advancement of fintech has brought changes to the business ecosystem, particularly regarding the ease of obtaining capital, the implementation of digital payment systems, and financial management practices among MSMEs. This study uses a quantitative method through a survey distributed to 120 MSMEs in Ternate City determined by purposive sampling technique. Data collection was carried out using a structured questionnaire, and data analysis was carried out using multiple linear regression using SPSS version 26 software. The independent variables in this study consist of the use of digital payment services (X1), access to fintech financing, and digital financial literacy, while the dependent variable is MSME performance which is assessed based on increased turnover, operational efficiency, and expansion of market reach. The findings of this study are expected to provide a comprehensive picture of the role of fintech adoption in supporting the development of MSMEs in Ternate City, while generating policy recommendations for the government and stakeholders to accelerate the digitalization of the economy at the local level